Burnout among hospital doctors working at a West Midlands Major Trauma Centre: a cross-sectional study - Alexandro Basso; Amy Attwater (Future Healthcare Journal, 2025)
Introduction: Since the introduction of burnout-related questions in 2018 by the General Medical Council (GMC) in their national training survey, risk of burnout has steadily increased, peaking in 2023.1 Given this, and the current workforce crisis in the NHS, where more doctors than ever are considering leaving the UK medical profession,2 it is important to consider whether burnout may play a role in a doctor’s decision to leave. The main aims of this study were to: (1) determine the prevalence of burnout among doctors; (2) investigate the association between sociodemographic variables, including thoughts on leaving the profession or the NHS, and both burnout and its two dimensions; and (3) examine the potentially predictive relationship between sociodemographic variables and burnout. Materials and methods: This cross-sectional study employed the Oldenburg Burnout Inventory (OLBI)3 to determine the prevalence of burnout as measured across its two core dimensions, exhaustion and disengagement, among doctors working at University Hospital Coventry, a major trauma centre located within the West Midlands. Participants were categorised into four burnout groups (burnout, exhausted, disengaged, and non-burnout) based on the mean exhaustion and disengagement scores. These groups were determined using the cut-off scores of ≥2.25 for exhaustion and ≥ 2.10 for disengagement as used in previous, comparable studies.4,5 In total, 156 doctors took part in an anonymised online questionnaire, which also gathered sociodemographic information. Results and discussion: 111 (71%) participants were categorised as experiencing burnout, 22 (14%) as exhausted, 7 (4%) as disengaged, and 16 (10%) as non-burnout. While there were no associations found between individual burnout groups and sociodemographic variables, significant associations were found between exhaustion and disengagement scores and professional grade (p <0.05 and p <0.001, respectively). Doctors who were in the earlier stages of their career were found to have significantly higher exhaustion and disengagement scores, a finding supported by correlation analysis (Table 1). There was a significant association between burnout group and thoughts on leaving the profession or NHS (p <0.001; Table 2). The predictive relationship between sociodemographic variables and burnout groups was found to be poor. Conclusion: While burnout is a persistent and prevalent issue that affects all doctors working at University Hospitals Coventry, statistically significant higher scores in the two burnout dimensions was seen in doctors who were earlier in their careers compared with more senior doctors. Additionally, those experiencing burnout had a statistically strong association with thoughts of leaving the profession or NHS. Given the current workforce crisis, more targeted interventions are needed by organisations to minimise burnout across its two core dimensions to ensure that current workforce trends are reversed.